Investment and economic growth in opening contexts: Problematic reality and stylized facts, Peru: 1990-2020 - Rijalba Palacios, Pablo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Evidence of the relationship between economic growth and investment is presented based on stylized facts of the Peruvian economy in the period 1990-2020. Applying descriptive, inferential and systematization methodologies to data from the BCRP and the World Bank, the behavior of public investment, foreign direct investment (FDI) and trade liberalization, among other variables, is analyzed. The levels, trends, correlations, and other indicators show facts that support the hypothesis that the relationship between public investment and private investment with growth is strong and direct, in contrast to the volatile relationship with Foreign Direct Investment (FDI).